Expressive Speech Act in the Novel Dialogue the Perfect Husband - Selviyani Selviyani; Tri Pujiati (Institut Agama Islam Negeri Palopo, 2019)
This research is aimed at describing the forms and the function of expressive utterances in the dialogue The Perfect Husband by Indah Riyana by using qualitative descriptive method. Based on data analysis, it is found that the forms and the function of expressive speech act in the novel dialogue The Perfect Husband by Indah Riyana consist of literal direct forms is 40 data (83,3%), the literal indirect form is 2 data (4,17%), the illiteral direct forms 4 data (8,3%), and the illiteral inderct form is 2 data (4,17%). The function of expressive speech act consist of thanks is 2 data (4,1%), asking for apology is 13 data (27,08%), praising is 5 data (10,41%), blaming is 9 data (18,75%), criticizing is 4 data (8,4%), quipping is 11 data (22,91%), and complaining is 4 data (8,4%).